Co-integration of major soybean markets in India: CO-INTEGRATION OF MAJOR SOYBEAN MARKETS IN INDIA - R VIJAYA KUMARI; SREENIVAS AKULA; RAMAKRISHNA GUNDU; VENKATESH PANASA (Journal of Oilseeds Research, 2021)
This study tested long-run spatial market integration between price pairs of soybean in five major markets viz., Indore, Nagpur, Kota, Bidar and Nizamabad of the India by adopting important econometric tools like Johansen’s multivariate Co-integration approach, Augmented Dickey-Fuller (ADF), Granger causality test, and Vector Error Correction Model (VECM). The study has confirmed the presence of co-integration, implying the five years price association among the markets. To get the additional evidence as to whether and in which direction price transmission is occurring between the market pairs, Granger causality test was used, which confirmed Indore to be the price-determining market. Indore was found comparativelymore efficient asit showed most bidirectional causal relations with other markets. The results showed that Indore market influenced the prices in the other two major markets i.e., Nagpur and Kota.